A Curriculum to Teach Learners How to Develop and Present a Case Report - Gina Luciano; Kathryn Jobbins; Michael Rosenblum (Association of American Medical Colleges, 2018)
Introduction Residents are required by the Accreditation Council for Graduate Medical Education to complete a scholarly project during residency, but they may not have dedicated time or instruction to be able to successfully achieve this goal. Methods In 2013 at Baystate Medical Center, we developed the Case Report Curriculum to guide internal medicine interns through the process of writing and presenting a case report. Core faculty and chief residents facilitate six sessions, which are scheduled throughout the year. Sessions combine large- and small-group discussion with facilitated independent work as well as postsession assignments and timely feedback from course facilitators. Topics include selecting a case report, crafting learning objectives, writing a discussion, authorship and creating a title, generating a poster, and presenting a poster. At the culmination of the conference series, interns present their completed case reports at an institutional academic day where judges critique and score their posters. Results Over the past 4 years, 95%-100% of our interns have participated in the required curriculum and presented their posters. We found that the majority of interns go on to present additional scholarly works at regional and national meetings during their second and third postgraduate years. Due to the success of the curriculum, interns from additional programs within the institution now attend the conference series. Discussion The Case Report Curriculum is a successful conference series that guides interns through the process of writing a case and can inspire additional scholarship during residency.